Gestão Social e Desenvolvimento Moral no Conselho Municipal de Saúde de Araguaína-TO Triênio 2018-2020 - SANTOS, Uallace Carlos Leal (Universidade Federal do Tocantins, 2024)
The research proposed to analyze the Municipal Health Council of Araguaína from theperspectives of Social Management and the Moral Development theory proposed by Kohlberg (1992). Seeking to present and discuss the ways in which public policy management councils were institutionalized in Brazil, their performance and importance in the democratic scenario; as well as the creation of the Municipal Health Council of Araguaína, its functioning and exercise. We also tried to analyze the characteristics of Social Management and Moral Development in the Council. Data collection occurred through quantitative and qualitative means, using bibliographic and documental research, as well as applying 14 questionnaires, 14 moral development tests and interviewing 3 members representing each area and analyzing 12 minutes. The minutes of the last Council meetings were analyzed, a questionnaire and moral development test were applied with 12 councilors, including members and alternates, user representatives, health workers, health service providers and government representatives. The research and analysis was based on the theories of Tenório et al. (2008) and Kohlberg (1992). Previously, the results indicate a good incidence of the exercise of deliberative citizenship, corroborating the good effectiveness of social management, however presenting a still low level, considered conventional, of psychic development of morality